2017
DOI: 10.1159/000478945
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated Care of Asthma in Switzerland (INCAS) Study: Changes in Asthma Control and Perception of Health Care through Asthma Education

Abstract: Background: Despite great efforts in establishing optimal asthma management, asthma may remain uncontrolled. To effectively manage chronic diseases, such as asthma, it is important to train patients in self-management skills. Objectives: The aim of this study was to assess the potential benefit of standardised asthma education in Switzerland for asthma control and patients' perception of received asthma care and of self-management support. Methods: For this multicentre longitudinal controlled study, asthma pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
(36 reference statements)
3
6
0
Order By: Relevance
“…Thus, 40% of the asthma patients indicated that their disease was not well-or poorly controlled while 30% of the COPD patients stated a high or very high impact of the ailment on their health status. These results are comparable to prior studies by Guénette et al, where 48% of the patients reported uncontrolled asthma [20] and by Dürr et al where 34% of the patients had uncontrolled asthma at baseline [21]. The mean CAT sum score was 16.7 in COPD patients at baseline, indicating a medium impact on health statusa value also observed in the PHARMACOP study, which examined the effectiveness of a pharmaceutical care programme in patients suffering from COPD [22].…”
Section: Patient Characteristicssupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, 40% of the asthma patients indicated that their disease was not well-or poorly controlled while 30% of the COPD patients stated a high or very high impact of the ailment on their health status. These results are comparable to prior studies by Guénette et al, where 48% of the patients reported uncontrolled asthma [20] and by Dürr et al where 34% of the patients had uncontrolled asthma at baseline [21]. The mean CAT sum score was 16.7 in COPD patients at baseline, indicating a medium impact on health statusa value also observed in the PHARMACOP study, which examined the effectiveness of a pharmaceutical care programme in patients suffering from COPD [22].…”
Section: Patient Characteristicssupporting
confidence: 87%
“…Not holding breath for about 5 s after inhalation a 6 (7) 1 (4) 1 developments in disease and therapy. This is particularly important in order to ensure that patients are continuously and actively involved in the treatment procedure [21]. Furthermore, these findings reconfirm the recommendation by the Global Initiative for Asthma (GINA) and Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines to regularly re-evaluate the correct device application to prevent faulty long-term device use [5,28].…”
Section: Inhalation Errorsupporting
confidence: 57%
“…This is particularly important in order to ensure that patients are continuously and actively involved in the treatment procedure [27]. Furthermore, these findings reconfirm the recommendation by the GINA and GOLD guidelines to regularly re-evaluate the correct device application to prevent faulty long-term device use [2,18].…”
Section: Device Application and Different Inhaler Typessupporting
confidence: 57%
“…While the structure as proposed by Glasgow et al was confirmed, no detailed results of the factor analysis were shown in this study [10]. Other previous studies used the PACIC-5A to evaluate chronic care, especially for diabetic and asthmatic patients [2023]. However, little is known about the underlying structure of the instrument so far.…”
Section: Introductionmentioning
confidence: 41%
“…In contrast, Glasgow et al revealed a comparably higher 5A summary score of 3.2 in a sample of diabetic patients and Rosemann et al showed a value of 2.5 among patients with osteoarthritis [10, 18]. In turn, one recently published study that used PACIC-5A among asthmatic patients in Switzerland revealed lower values of 2.0 for overall PACIC score and 5A summary score at baseline [23]. The lower scores in the present study were accompanied by high floor effects.…”
Section: Discussionmentioning
confidence: 99%